Crossing Borders, Translating Encounters: Moroccan Ambassadorial Travellers to Europe and the Linguistic Negotiation of Alterity - BEKKAOUI, Salaheddine (International Journal of Linguistics and Translation Studies, 2023)
The Moroccan ambassadorial travel narratives to Europe display an interesting interplay between the processes of translation and cross-cultural exploration. As these travellers embarked on their journeys, they embraced a versatile approach to translation, employing their native language, borrowing foreign loanwords, and transliteration techniques to grapple with the enigmatic manifestations of the alien world they visited. This intricate process, the paper argues, not only reflects their determination to comprehend the unfamiliar landscapes and exotic people they encountered but also highlights their inherent curiosity about European culture and civilization. The other conclusion is that the act of translation within their narratives embodies their conscious efforts to convey the essence of their experiences to audiences back home who lacked the opportunity to embark on similar journeys.